Design of a frequency-energy independent nonlinear oscillator - Jerschl, Martin; Willner, Kai (35th IMAC Conference and Exposition on Structural Dynamics, 2017, 2017)
A method for the design of a frequency-energy independent nonlinear oscillator, for example a jointed system, is presented. Usually, nonlinear dynamic systems are energy dependent. For a geometrically nonlinear system the eigenfrequency increases with rising energy in the system. For a friction damped system the opposite is the case. These two contrary behaviours of nonlinear system types are used to design a frequency-energy-independent system. The HILBERT-transform is used as a design tool in combination with the Multi-Harmonic-Balance-Method (MHBM). An approach for automated design is introduced.
Keywords: Friction; Hilbert transform; Nonlinear dynamics; Nonlinear normal modes (NNMs); Optimal system design